2020
DOI: 10.1097/mrr.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Establishing K-levels and prescribing transtibial prostheses using six-minute walk test and one-leg standing test on prosthesis: a retrospective audit

Abstract: Rehabilitation programs after amputation often include fitting a prosthesis, but prescriptions vary under similar circumstances. The US Medicare Functional Classification Level (K-level) is a scale for describing functional abilities of persons after lower-limb amputation (from 0 = no ability or potential to ambulate, to 4 = prosthetic demands of a child/active adult/athlete). Different outcome measures are used to assess K-level, including six-minute walk test (6MWT). We attempted to predict the assigned K-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
“…Studies that explicitly stated limitations or confounders were just over two-thirds of the total (Table 2),. 13,14,19–22,24,28–56,71,74,76,77,80–95,108,109,115–132,140–145,147–165,169–180,182–184,188–191,193–198 The most commonly mentioned limitation was small sample size, 20,22,24,28,29,32,33,35,37,39,40,42,45,47,52,54-57,74,80,82,86,87,89,93,95,109,118,119,121,123,126,129,141,143,145,148,149,154-159,161,164,169,172,183,198 followed by generalizability issues, 14,19-21,34,38,41,42,44,52-56,80,81,87,89,109,127-130,142,148,151,155,156,162,171,175-177,184,188,189,191,193,196 recall bias, 14,148,150,157,171,173,182,184 heterogeneous groups, 29,42,54,89,142,174,176,177 homogenous groups, 21,38,39,44,45,91,164 and convenience samples. 14,161,176,177,196…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…THE 6-MINUTE WALK TEST (6MWT) is a generic timed test used to assess aerobic capacity and endurance, and to monitor prosthetic walking performance [9]. It measures the distance an individual is able to cover over 6 min on a hard, flat surface.…”
Section: Performance-based Measurementioning
confidence: 99%
“…Also, the Prosthetic Mobility Questionnaire (PMQ) in its original [4] and revised version (PMQ 2.0) represents a recent Rasch-validated refinement of the PEQ-MS, with even better psychometric characteristics [5]. Other tools are the Activities-specific Balance Confidence Scale (ABC-5), a self-report measure of confidence in performing various activities without falling [6,7], and the 6-Minute Walk Test (6MWT), a performance-based measure of mobility (distance walked in a fixed time) [1,8,9].…”
Section: Introductionmentioning
confidence: 99%